Could Global Intensification of Nitrogen Fertilisation Increase Immunogenic Proteins and Favour the Spread of Coeliac Pathology? - Josep Penuelas; Albert Gargallo-Garriga; Ivan A. Janssens; Philippe Ciais; Michael Obersteiner; Karel Klem; Otmar Urban; Yong-Guan Zhu; Jordi Sardans (Foods, 2020)
Fertilisation of cereal crops with nitrogen (N) has increased in the last five decades. In particular, the fertilisation of wheat crops increased by nearly one order of magnitude from 1961 to 2010, from 9.84 to 93.8 kg N ha−1 y−1. We hypothesized that this intensification of N fertilisation would increase the content of allergenic proteins in wheat which could likely be associated with the increased pathology of coeliac disease in human populations. An increase in the per capita intake of gliadin proteins, the group of gluten proteins principally responsible for the development of coeliac disease, would be the responsible factor. We conducted a global meta-analysis of available reports that supported our hypothesis: wheat plants growing in soils receiving higher doses of N fertilizer have higher total gluten, total gliadin, α/β-gliadin, γ-gliadin and ω-gliadin contents and higher gliadin transcription in their grain. We thereafter calculated the per capita annual average intake of gliadins from wheat and derived foods and found that it increased from 1961 to 2010 from approximately 2.4 to 3.8 kg y−1 per capita (+1.4 ± 0.18 kg y−1 per capita, mean ± SE), i.e., increased by 58 ± 7.5%. Finally, we found that this increase was positively correlated with the increase in the rates of coeliac disease in all the available studies with temporal series of coeliac disease. The impacts and damage of over-fertilisation have been observed at an environmental scale (e.g., eutrophication and acid rain), but a potential direct effect of over-fertilisation is thus also possible on human health (coeliac disease).